Analisis Keterbukaan Diri (Self-Disclosure) Siswa Laki-Laki Kepada Guru BK di SMA Negeri 01 Pulau Maya - Mat Yusuf; Muhammad Asrori; Amallia Putri (Pusat Riset dan Inovasi Nasional, 2025)
Self-disclosure is an interpersonal communication process in which individuals voluntarily share personal information that is typically unknown to others. This research focuses on the self-disclosure of male students to Guidance and Counseling teachers at SMA Negeri 1 Pulau Maya, aiming to explore the factors influencing their openness and its impact on their personal and emotional development. Using a quantitative descriptive approach, the study collected data from 33 male students through a questionnaire based on a Likert scale. The results revealed that the students demonstrated a high level of self-disclosure with a score of 87.04%, indicating a strong sense of comfort and trust in sharing personal thoughts, feelings, and experiences with their BK teacher. The study also found that both internal factors, such as self-confidence and social acceptance, and external factors, such as supportive school environments and teacher-student relationships, significantly contributed to students' openness. The findings support previous research that self-disclosure promotes emotional well-being and stress management. Based on these results, it is recommended that teachers create a safe and supportive environment to encourage self-disclosure, helping students develop better emotional and social skills. Furthermore, more programs that facilitate open communication, such as group counseling sessions, should be implemented to support students' personal development.